Visible Photon Emission From Defects in Hexagonal Boron Nitride Flakes - Fırat, Volkan; Ateş, Serkan; Ateş, Serkan (Izmir Institute of Technology, 2017)
Geniş band aralığına sahip kristallerde bulunan renk merkezleri, band aralığı içerisinde kesikli enerji seviyeleri oluşturur. Bir çok kuantum optik ve kuantum bilgi uygulamaları için gerekli olan tek-fotonlar bu kesikli enerji seviyeleri kullanılarak elde edilebilir. Bu çalışmada, çok katmalı hekzagonal bor nitrür (hBN) pulları içinde, tavlama tekniği kullanılarak optik-aktif kusurlar oluşturuldu. Farklı tavlama sıcaklıklarında (500, 750 ve 850°C) yedi örnek ve kıyaslama için iki tavlanmamıs¸ örnek hazırlandı. hBN geniş band aralığı sayesinde görünür bölgede ışıma yapan kusurları barındırabilir. hBN pulları içerisindeki noktasal kusurları bulmak için mikro-fotolüminesans haritalama yapıldı. Daha sonra uyarma gücüne, polarizasyona ve sıcaklığa bağlı ölçümler yapıldı. Ölçümler sonucunda kusurların ortalama 0.5 m boyutlarında olduğu, göreceli olarak düşük uyarma güçlerinde doyuma ulaştıkları, dipole özellik gösterdikleri, 0.8 meV kadar dar genişlikte sıfır-fonon çizgisine sahip oldukları gözlemlendi. Bu sonuçlar kesikli enerji seviyelerine sahip, optik-aktif kusurların oluştuğunu göstermektedir.

Color centers in wide bandgap crystals create discrete energy levels in the bandgap. These discrete energy levels can be used for single photon generation for quantum optics and quantum information applications. In this work, we created optically active defects in multilayer hexagonal boron nitride (hBN) flakes by annealing technique. We produced seven samples at different annealing temperatures (500°C, 750°C and 850°C) and two non-annealed samples for comparison. hBN can host defects emitting at visible wavelengths because of its wide bandgap. We made micro-photoluminescence maps to find point defects in the hBN flakes and then carried out power dependent, polarization dependent and temperature dependent measurements to characterize the emissions. We observed highly localized point-like emitters with a size of about 0.5 m that reach saturation at relatively low excitation powers, show dipole characteristics, have very narrow zero-phonon lines having widths as small as 0.8 meV . These results prove the presence of optically active defects with discrete energy levels.
Hekzagonal Bor Nitrür Pullarındaki Kusurlardan Görünür Foton Işıması
Thesis (Master)--Izmir Institute of Technology, Physics, Izmir, 2017
Includes bibliographical references ( leaves. 35-38)
Text in English; Abstract: Turkish and English
xi, 49 leaves
Keywords: Point defect; Optical emission; Hexagonal boron nitride